Perspectives of Stem Cells From tools for studying mechanisms of neuronal differentiation towards therapy - Ulrich, Henning; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
The field of stem cell biology is geared towards translation into clinical practice through in vitro tissue production and regeneration therapy. Since the discovery of adult neurogenesis, much attention has been put on the study of differentiation of stem cells into neural cell types and the development of model systems for stroke and neurodegenerative diseases. In addition to chapters on therapeutic applicability of embryonic, very small-embryonic like, mesenchymal stem and neural progenitor cells, this book covers signalling mechanisms guiding induction to differentiation and cell diversification. Furthermore, fundamental aspects of stem cell biology and neurogenesis, such as the importance of proliferation induction, programmed cell death and the function of glia in differentiation of stem cells and development of neuronal circuits, are also highlighted. In vitro cultures of embryonic, mesenchymal and neural stem cells as well as mobilization of endogenous stem and precursor cells for brain repair and replacement therapy in neurological disorders are important issues of this book. Each chapter is written by researchers who are leaders in the field and provides an invaluable resource for information on the most current advances in the field and possible therapeutic applications, with discussions of controversial issues and areas of emerging importance. By providing an up-to-date and critical view of the state of Science, we hope that this book shall be a base for exciting scientific ideas regarding functions and therapeutic applications of stem cells in the adult brain. The book is directed to neuroscientists, physicians, students and all who are engaged and interested in the exciting and rapidly expanding field of modern neuroscience and stem cell biology.
Neural Induction -- Neurogenesis: A Change of Paradigms -- Neurogenesis in the Olfactory Epithelium -- Cell Diversification During Neural Crest Ontogeny: The Neural Crest Stem Cells -- Intermediate Filament Expression in Mouse Embryonic Stem Cells and Early Embryos -- Aneuploidy in Embryonic Stem Cells -- Retrotransposition and Neuronal Diversity -- Directing Differentiation of Embryonic Stem Cells into Distinct Neuronal Subtypes -- Neurotransmitters as Main Players in the Neural Differentiation and Fate Determination Game -- Rhythmic Expression of Notch Signaling in Neural Progenitor Cells -- Neuron-Astroglial Interactions in Cell Fate Commitment in the Central Nervous System -- The Origin of Microglia and the Development of the Brain -- Tissue Biology of Proliferation and Cell Death Among Retinal Progenitor Cells -- Potential Application of Very Small Embryonic Like (VSEL) Stem Cells in Neural Regeneration -- Embryonic Stem Cell Transplantation for the Treatment of Parkinson's Disease -- Functional Multipotency of Neural Stem Cells and Its Therapeutic Implications -- Dual Roles of Mesenchymal Stem Cells in Spinal Cord Injury: Cell Replacement Therapy and as a Model System to Understand Axonal Repair.
Keywords: Life sciences; Medicine; Neurosciences; Neurochemistry; Stem cells; Developmental biology; Life Sciences; Stem Cells; Neurosciences; Developmental Biology; Neurochemistry; Biomedicine general